Disturbios neuropsicológicos e síndrome da apneia do sono em crianças - Hilario, Silvana Maria; Silva, Érico Vinícius Campos Moreira da [UNESP]; Chiloff, ristiane Lara Mendes [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Micheletti, Kelly Regina [UNESP]; Cuoghi, Osmar Aparecido [UNESP]; Weber, Silke Anna Theresa [UNESP] (My University, 2014)
Obstructive Sleep Apnea Syndrome (OSAS) is characterized by snoring and / or repetitive pauses in breathing during sleep associated with hypoxemia and hypercapnia. Affects approximately 1-3% of children, especially preschoolers. There is an association of OSAS with negative impact on neurocognitive development. However, there are few studies using protocols to assess cognition and behavioral disorders in children with OSAS. The objective of this study was to analyze the major studies related to the topic within the last two decades. The main studies published between 1995 to 2011 were identified through MEDLINE and LILACS databases. We selected the most relevant for OSAS in children, neurocognitive effects and association between obstructive disorders / OSAS in the target population (children). It was concluded that the studies analyzed showed that there is strong evidence regarding the overlapping of OSAS in children with neurocognitive disorders and that treatment of OSAS has positive impact on neurocognitive development.

El Síndrome de Apnea Obstructiva del Sueño (SAOS) se caracteriza por ronquidos y / u pausas en la respiración durante el sueño asociado con hipoxemia e hipercapnia. Afecta a aproximadamente el 1-3% de los niños, especialmente en edad preescolar. Hay una asociación de SAOS con un impacto negativo en el desarrollo neurocognitivo. Sin embargo, hay pocos estudios que utilizan protocolos para evaluar los trastornos cognitivos y de comportamiento en los niños con SAOS. El objetivo de este estudio fue analizar los principales estudios relacionados con el tema en las últimas dos décadas. Los principales estudios publicados entre 1995-2011 fueron identificados a través de las bases de datos MEDLINE y LILACS. Hemos seleccionado los más relevantes para el SAOS en los niños y en los efectos neurocognitivos y asociación entre los trastornos obstructiva / SAOS en la población objetivo (niños). Se concluyó que los estudios analizados mostraron que existe una fuerte evidencia respecto a la superposición de SAOS en los niños con trastornos neurocognitivos y que el tratamiento de la SAOS tiene un impacto positivo en el desarrollo neurocognitivo.

A Síndrome da Apnéia Obstrutiva do Sono (SAOS) é caracterizada por ronco e/ou pausas respiratórias observadas durante o sono associado à hipoxemia e hipercapnia. Afeta cerca de 1 a 3% das crianças, principalmente em idade pré-escolar. Há associação de SAOS com impacto negativo no desenvolvimento neurocognitivo. Porém, ainda há poucos estudos utilizando protocolos para avaliar a cognição e distúrbios comportamentais em crianças portadoras de SAOS. O objetivo do presente trabalho foi analisar os principais estudos relacionados ao tema dentro das duas últimas décadas. Os principais trabalhos publicados no período de 1995 a 2011 foram identificados por meio da base de dados MEDLINE e LILACS. Foram selecionados os mais relevantes sobre SAOS em crianças, repercussões neurocognitivas e associação entre distúrbios obstrutivos/SAOS na população alvo (crianças). Concluiu-se que os trabalhos analisados indicaram que há fortes evidências quanto à sobreposição de SAOS aos distúrbios neurocognitivos na criança e que o tratamento de SAOS tem repercussão positiva no desenvolvimento neurocognitivo.
Neuropsychological disorders and sleep apnea syndrome in children
Trastornos neuropsicológicos y el síndrome de apnea del sueño en niños
Keywords: Apnea; Nasal obstruction; Sleep; Child; Cognition; Apnea; Obstrucción nasal; Sueño; Niño; Cognición; Apneia; Obstrução; Sono; Criança; Cognição